Synthesis of 1‐Naphthol by a Natural Peroxygenase Engineered by Directed Evolution. (21st January 2016) - Molina‐Espeja, Patricia; Cañellas, Marina; Plou, Francisco J.; Hofrichter, Martin; Lucas, Fatima; Guallar, Victor; Alcalde, Miguel
Abstract: There is an increasing interest in enzymes that catalyze the hydroxylation of naphthalene under mild conditions and with minimal requirements. To address this challenge, an extracellular fungal aromatic peroxygenase with mono(per)oxygenase activity was engineered to convert naphthalene selectively into 1‐naphthol. Mutant libraries constructed by random mutagenesis and DNA recombination were screened for peroxygenase activity on naphthalene together with quenching of the undesired peroxidative activity on 1‐naphthol (one‐electron oxidation). The resulting double mutant (G241D‐R257K) obtained from this process was characterized biochemically and computationally. The conformational changes produced by directed evolution improved the substrate's catalytic position. Powered exclusively by catalytic concentrations of H2 O2, this soluble and stable biocatalyst has a total turnover number of 50 000, with high regioselectivity (97 %) and reduced peroxidative activity. Abstract : A self‐sufficient UPO mutant : An aromatic peroxygenase was engineered to synthesis 1‐naphthol. Modification of the ratio of peroxidative and peroxygenase activity produced an evolved enzyme with a total turnover number of 50 000 and high selectivity. This biocatalyst represents a promising one‐pot alternative for replacing the currently prevailing polluting chemical processes to meet industrial demands for 1‐naphthol synthesis.